Potential of fabricated light foamed concrete in reducing radon from building material - Syahrul Affandi Saidi; Mohamad Suhaimi Jaafar; Mohammad Khairul Azhar Abdul Razab; Mohd Sukhairi Mat Rasat; Muhammad Iqbal Ahmad; Mazlan Mohamed; Sarizam Mamat; Hamzah Hussin (2016)
Three of Light Foamed Concrete (LFC) have been obtain by using different formula of Cement:Aggregates. The brick was locate into a closed Perspex box and the net of 222Rn concentration level have been measured for 5 consecutive days. The results show the LFC 3 has produced the lowest of net 222Rn concentration level in air, followed by LFC 2 and LFC 1, respectively. The result also show the 222Rn concentration level have been influenced by the temperature and relative humidity in air.